Sistema de creación de micrositios de contenido dinámico embebidos en la página de la ESPAM MFL - Mera Domínguez, Jefferson Adrián (2021)
The objective of this work on curricular integration was to develop a web system for the creation of dynamic content microsites for the Technology Unit at ESPAM MFL, in order to automate the dissemination of information from institutional departments through modules. The methodology used was Extreme Programming (XP), with each of its phases (planning, design, coding and tests) that facilitated the preparation of the work, in the planning phase each of the user stories, the diagrams of use cases and the estimation of development time through the iterations plan, taking as a reference the requirements obtained in the interviews carried out, in the design phase the data model, the class diagram and the interfaces of the coding phase, the modules were programmed using the computer tools used by the Technology Unit to create its software products, such as the Visual Studio IDE, the ASP.NET environment, the C # programming language and the SQL Server database manager. Lastly, in the testing phase, the correct operation of the system was verified through unit and black box tests. As a result, a system was obtained that allows a more agile and faster process in the creation, use and management of microsites, complying in a timely manner with the demand for requirements requested in the Technology Unit.